2014
DOI: 10.1016/j.infbeh.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Not just playing around: Infants’ behaviors with objects reflect ability, constraints, and object properties

Abstract: This study describes infants’ behaviors with objects in relation to age, body position, and object properties. Object behaviors were assessed longitudinally in 22 healthy infants supine, prone, and sitting from birth through 2 years. Results reveal: (1) infants learn to become intense and sophisticated explorers within the first 6 months of life; (2) young infants dynamically and rapidly shift among a variety of behavioral combinations to gather information; (3) behaviors on objects develop along different tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 46 publications
(79 reference statements)
0
25
0
Order By: Relevance
“…For instance, increasing stability and flexibility in sitting supports object manipulation and exploration activity by expanding the manual movement repertoire as well as supporting the coordination of looking while exploring (Perone, Modole, Ross-Sheehy, Carey, & Oakes, 2008; Soska et al, 2010; Spencer, Vereijken, Diedrich, & Thelen, 2000). For instance, Lobo and colleagues found that object manipulation did not differ in supported sitting in comparison to supine positions (Lobo, Kokkoni, de Campos, & Galloway, 2014). However, experience in sitting without support has been found to relate to visual coordinated object manipulation (Soska et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, increasing stability and flexibility in sitting supports object manipulation and exploration activity by expanding the manual movement repertoire as well as supporting the coordination of looking while exploring (Perone, Modole, Ross-Sheehy, Carey, & Oakes, 2008; Soska et al, 2010; Spencer, Vereijken, Diedrich, & Thelen, 2000). For instance, Lobo and colleagues found that object manipulation did not differ in supported sitting in comparison to supine positions (Lobo, Kokkoni, de Campos, & Galloway, 2014). However, experience in sitting without support has been found to relate to visual coordinated object manipulation (Soska et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 By 6 months, infants have already become sophisticated in exploring objects with high intensity, variability, and combinations of behaviors. 8 After 6 months, infants continue to explore objects using a range of behaviors, such as fingering, picking, and looking, and these behaviors are exhibited differently in relation to the properties of objects. 9 -11 Despite the fact that object exploration behaviors are considered important precursors for global development, surprisingly few studies have been done to assess these behaviors in populations at risk for future developmental delays, such as infants born preterm.…”
mentioning
confidence: 99%
“…22, 23, 24, 25 Children typically learn about objects by interacting with them a large amount of the time via a variety of behavioral combinations. 17 The amount and variability of behavioral performance, and consequent information uptake and learning, is often diminished for children with disabilities. 18, 26, 27, 28 Devices like the P-WREX may allow young children to explore, gather information, play, and learn when it is critical in early development despite their existing movement limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The types of behavioral analyses used in this study are well-established methods widely used in developmental research. 15, 16, 17, 18 …”
Section: Methodsmentioning
confidence: 99%